Review of Dispute Resolution of Heritage Assets and Administration of A Will in Evidence of Disputes - Irpan Irpan (Sultan Agung Notary Law Review, 2020)
The purpose of this study is to determine and analyze: 1) Legal construction for the making of wills in the planning of distribution of inheritance. 2) The roles and responsibilities of a notary in the execution of a will. 3). The position of the will in proving inheritance disputes at the Kendari Religious Court based on Decision No.384.Pid.B/2018/PN.Kdi. This research is a juridical-normative approach which is derived from data collection obtained from primary data and secondary data, then analyzed by qualitative analysis methods. Data collection techniques by interview and literature study, data analysis using qualitative analysis. The results of the research are: 1) Legal construction for the making of wills in the planning of distribution of inheritance, namely wills must be written in the form of a will, this is in accordance with the provisions in article 921 of the Civil Code and confirmed in article 195. KHI states that a will is the gift of an object from the heir to another person or institution which will take effect after the heir dies. 2) The role and responsibility of the notary in making a will, namely the notary has the duty and obligation to list the deeds relating to the will. If the notary fails to carry out his responsibilities, the Notary may be subject to sanctions in the form of: written warning; temporary suspension; honorific dismissal; or dishonorable dismissal. 3). The position of wills in proving inheritance disputes at the Kendari Religious Court based on Decision No.384.Pid.B/2018/PN.Kdi, namely wills are used by judges as strong evidence, because they have been made clearly and also legalized by a notary Will deed drawn up by a notary, which is used as evidence in order to have perfect evidentiary power.